ANALISIS PENDAPATAN BERBASIS KAS DAN BERBASIS AKRUAL DALAM LAPORAN KEUANGAN PEMERINTAH DAERAH - Monica Valencia Putri; Rindu Rika Gamayuni; Komaruddin Komaruddin; Fitra Dharma (Jurnal Akuntansi dan Keuangan (JAK), 2021)
This study aims to examine cash basis income (LRA-income) and accrual basis income (LO-income) in the financial statement of provincial gov ernments in Indonesia. The sample in this study used 33 provinces in Indonesia within a period of 10 years from 2010-2019. The results of this study indicate that there is a significant difference in the increase in the total income of LRA-LRA and LRA-LO in provincial LKPD in Indonesia before and after the application of accrual based SAP. There is a significant difference in the increase in local revenue of LRA-LRA and LRA-LO in provincial LKPD in Indonesia before and after the application of accrual-based SAP. There is a significant difference in the increase in local taxes LRA-LRA and LRA-LO in provincial LKPD in Indonesia before and after the application of accrual-based SAP. There is a significant difference in the decrease in regional levies LRA-LRA and LRA-LO in provincial LKPD in Indonesia before and after the application of accrual-based SAP.Keywords: cash basis income, accrual basis income, accrual-based SAP, LRA-Income and LO-income